Evaluation of eutectic lidocaine/prilocaine cream for jugular blood sampling in cats. Issue 2 (February 2021) - Crisi, Paolo E; De Santis, Francesca; Giordano, Maria V; Cerasoli, Ilaria; Colucci, Fabrizio; Di Tommaso, Morena; Luciani, Alessia
Objectives: The study aimed to evaluate the efficacy of a eutectic lidocaine/prilocaine cream (EMLA cream; Astra Pharmaceuticals) in reducing pain and reaction to venepuncture during jugular blood sampling in cats after a 30-min topical application time. Methods: The study was a prospective, blind, controlled clinical trial. Eighteen healthy client-owned cats were randomly allocated to two study groups. All cats were clipped on the left jugular groove region and then, depending on the study group, either the placebo (liquid paraffin) or EMLA cream was applied to the region. The area was then kept protected for the next 30 mins. Except for the operator who administered the product, all operators were blinded to the study groups. Blood sampling was performed by an experienced operator and a stress score was assigned to each cat according to the reactions observed during the venepuncture. Also, the procedure was classified as being 'easy' or 'difficult' by the same operator. Results: A significantly reduced stress score was observed in cats that received the EMLA cream compared with those belonging to the placebo group ( P = 0.048); withdrawal movements were observed in 1/9 cats treated with the EMLA cream vs 7/9 cats of the placebo group ( P = 0.015). The jugular venepuncture was defined as easy in 1/9 cats that received the placebo and in 8/9 cats in the EMLA group ( P = 0.015). Conclusions and relevance: The present study provides evidence for the efficacy of the EMLA cream after a 30-min application time for jugular venepuncture in cats, together with significantly reduced stress for patients. Therefore, this study supports the routine use of EMLA cream as good practice to enhance the welfare of cats and to simplify venepuncture procedures.